Urological Services in the Era of COVID-19 - Efthimiou, Ioannis (Urology Journal, 2020)
INTRODUCTION: On 11 March 2020, the World Health Organization (WHO) declared a pandemic. Since then hospitals have reduced inpatient and outpatient workflow and cancelled or suspended all non-emergent and routine surgical procedures. Our objective is to determine whether, during the COVID-19 period, there has been any modification in urological services. MATERIALS AND METHODS: We retrospectively studied the data from January-May 2020 and 2019 about the variables: number of operations, waiting list, visits in outpatient department, bladder instillations and urological emergencies and admission rates. RESULTS: Cancer cases high-risk for stage progression and surgical emergencies, were elected to proceed directly to treatment. The number of the operations was reduced by 43-65% from March-May 2020. Our surgical list had a waiting time of 6-8 weeks before the pandemic and now the waiting time has expanded to 12 weeks. Urological emergencies were reduced about 23-57%. Admission rates were dropped 10-51%. Visits in outpatient clinics were reduced 100-50% and outpatient procedures for elective cases were all deferred. Unfortunately, the hospital did not offer synchronous telehealth appointments. Bladder instillations of BCG or chemotherapeutics were not suspended but start of new cases had a delay of 2-3 weeks. There were no cases of COVID-19 in our department. CONCLUSION: All the variables of our urologic practice were affected during the COVID era. The impact of the reduced model of outpatient and inpatient workflow on the health of our patients is unknown. However, longer waiting lists are expected. It is obvious that healthcare providers should adopt a new healthcare model.